Sharia Perspective Supervision Management in Preventing Corruption - Asmaul Husna (Universitas Muhammadiyah Sumatera Utara, 2021)
Corruption has evolved into a difficult-to-control problem, particularly in Indonesia, where the problem is growing in both quantity and quality. As the number of corruption cases grows, so will the amount of money lost by the government. Indeed, both at the national and provincial levels, this criminality has been rampant. Local government personnel have more opportunity to conduct illegal acts of corruption as a result of the government's decentralization scheme. This problem necessitates an assessment in order to identify guidelines that may be used to avoid corruption, therefore this study focuses on the supervision of public policy in the fight against corruption through community participation. The major issue addressed in this study is how effective public policy oversight is in combating corruption through public participation. This study employs a descriptive analysis research method to address this issue, allowing it to be concluded that the public plays a role in monitoring public policies regarding corruption prevention through efforts to prevent and eradicate corruption crimes, based on the information presented in the discussion. This oversight is carried out to ensure that public policy is carried out in conformity with its stated goal, namely the prevention of criminal corruption. Individuals, non-governmental groups, and other types of community organizations can all play a role in achieving community engagement.